Take no prisoners : a no-holds-barred approach to corporate excellence - Davis, Marvin A. (AMACOM, 2008)
Now more than ever, American companies are experiencing a nagging feeling that they could be doing much better. Globalization, digitization, and the development of cellular technology have increased competition by leaps and bounds. As a consequence, skating by on marginal performance isn't enough. It's time for businesses to find the tools that will help them excel. A turnaround expert, Marvin Davis has made a career out of transforming underperforming companies. He assesses their mistakes, issues a diagnosis, and has helped allay the fears of many CEOs across the country -- leaving businesses more efficient and ultimately more competitive. In Take No Prisoners, he gives hard-line, tough-love solutions to the real and difficult problems that hinder profitability. By addressing issues that may at first seem too messy or dangerous, companies can learn how to truly improve performance, increase profits, and boost cash flow. Companies shouldn't wait until they are in dire straits to make changes; they can alleviate many problems if they act now and meet them head-on. Through real-life examples of corporations who have made these solutions work successfully, Take No Prisoners tells American companies the truth about the state of their business, and how to make it even better.